Teknik Dasar Fotografi Untuk Tingkat Pemula - Darma, Surya; Mulya, Mhd. Ade (LPPM Universitas Potensi Utama, 2022)
Today, the development of the world of photography in Indonesia has experienced a significant development. Various branches of the art of photography began to emerge such as Landscape Photography, Macro Photography, Street Photography, Portrait Photography, Journalist Photography and Fashion Photography. Photography is not only limited to word for word definitions, but in a broader scope can be interpreted as a process of taking pictures with camera media, creating styles, techniques and then changing them in an image. Basic photography techniques for beginner level providing training to Admin Ma'had Tahfidz Yatim Dhuafa Kitabina Medan are needed as a need for donation reports from the Fadhilatul Quran Foundation Aceh. Based on direct observations in the field, this community service activity provides results to explain how Basic Photography Techniques for Beginner Level at Ma'had Tahfidz Yatim Dhuafa Kitabina Medan, and is useful for producing photo donation reports with Basic Photography Techniques for Beginner Level at Ma' had Tahfidz Yatim Dhuafa Kitabina Medan. The results of this community service activity provide the conclusion that Basic Photography Techniques for Beginners provide the final result as a donation report to Ma'had Tahfidz Yatim Dhuafa Kitabina Medan, Community service that has been carried out has attracted the interest of several elements involved in Ma'had Tahfidz Kitabina Medan, Admin Ma'had Tahfidz Yatim Dhuafa Kitabina Medan can understand the basic techniques of photography at the beginner level at Tahfidz Yatim Dhuafa Kitabina Medan as a donation report